Stability of quantum linear logic circuits against perturbations. (14th October 2020) - Babushkin, Ihar; Morgner, Uwe; Demircan, Ayhan
Abstract: Here we study transformation of waveshapes of photons under the action of the linear logic circuits and other related architectures involving only linear optical networks and measurements. We show that the gates are working well not only in the case when all photons are separable and located in the same mode, but in some more general cases. For instance, the photonic waveshapes are allowed to be slightly different in different channels; in this case, Zeno effect prevents the photons from decoherence after the measurement, and the gate thus remains neutral to the small waveshape perturbations.